Iterative Schemes for a Class of Mixed Trifunction Variational Inequalities - Muhammad Aslam Noor; Khalida Inayat Noor; Eisa Al-Said (Journal of Applied Mathematics)
We use the auxiliary principle technique to suggest and analyze some iterative methods for solving a new class of variational inequalities, which is called the mixed trifunction variational inequality. The mixed trifunction variational inequality includes the trifunction variational inequalities and the classical variational inequalities as special cases. Convergence of these iterative methods is proved under very mild and suitable assumptions. Several special cases are also considered. Results proved in this paper continue to hold for these known and new classes of variational inequalities and its variant forms.